(3OQQ GdahGFO hZQQ GdaQGFO ddeSJQTO GdbGUO Edi CSfi GdebGUOs - (3UOjb Hf eYQha GdaRjfj GdeTQYj Gdjefj,J (B912 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO CeG HYO aEfg deG cGfJ GdebGUO hGdeWGdH cKjQI eNJdaI cKQI dCLd Pdc GdWQb hGNJdaJ ajSQ Gddg JCdja gPG GdeNJUQ GdeSei HOQQ GdahGFO hZQQ GdaQGFO s
(3BNQgG (B:s
(3hbGd CjVkG Yde GdJhMjO eHGjf dhLhOg hhLhOg eaGQb dYdeg hbGd CjVkG eGTe QhGFM GdJhMjO ef JUhQ YfOg GdJhMjO hGddg CYde Je GdcJGH HMeO Gddg JYdi hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B468s
Keywords: (3GdJhMjO hGdedd hGdfMds